Impartiality, gender stereotypes and judiciary corruption - Villanueva Flores, Rocío (2021)
This article analyzes gender stereotypes in legal reasoning in contexts of severe judiciary corruption, which results in the violation of impartiality. The author maintains that it is the impunity of judiciary corruption, associated with structural  iscrimination, which largely explains the cynicism in legal rulings on gender violence. She also proposes that judicial virtues are essential to face corruption in the judicial arena.